Mine completion criteria defined by best-practice: A global meta-analysis and Western Australian case studies - Manero, A.; Standish, R.; Young, Renee (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2021)
In many mining-intensive areas around the world, knowledge-sharing among companies is critical to advance best-practices in mine rehabilitation and closure. The academic literature documents innovative, best-practices options, yet these are often not accessible to field practitioners. Published mine closure plans provide relevant examples of standards accepted by regulators, however, regulations vary with jurisdiction and can change over time, limiting the utility of these plans. There is, therefore, a need for greater transparency and accessibility of practical knowledge to inform the definition of achievable completion criteria. The purpose of this study is to provide an overview of best-practices for the purpose of defining mine completion criteria. The methods comprise: i) a qualitative meta-analysis of the global peer-reviewed literature; and ii) three in-depth case studies in Western Australia. The research identifies ten key best-practices that could be potentially applied by mining proponents to guide the definition of successful completion criteria. These include: multiple references, monitoring and corrective actions, science-informed completion criteria, holistic rehabilitation, dynamic targets, leading indicators, integration of rehabilitation with mine operations, innovation-guided completion criteria, specific objectives and indicators and risk-based completion criteria. These best-practices are further examined through recent mine rehabilitation and closure programs of mid-to-large mining operators in Western Australia. Our findings provide the first comprehensive review of best-practices towards the definition of mine completion criteria, which are relevant to industries requiring rehabilitation of disturbed lands across Australian and international jurisdictions.